Integrated Skills Approach in Elementary EFL Classrooms: Teachers' Perceptions and Implementation Practices - Satriabudhi, Muhammad Ariyudha Rio; Ilyas, Hamzah Puadi (Jurnal Ragam Pengabdian, 2026)
Integrated skills instruction is widely recommended for EFL classrooms, yet elementary English teaching in Indonesia often remains segregated. This study investigates how elementary EFL teachers perceive the Integrated Skills Approach (ISA), implement it in classroom planning, and what type of integration they use. A qualitative case study was conducted at SD Mutiara Bangsa 2, Tangerang City, involving three English teachers with over seven years of experience. Data were collected through interviews, questionnaires, and lesson-plan documentation, then analyzed descriptively and thematically. The findings indicate that teachers perceived ISA positively as an approach that improves communicative competence, activates classroom interaction, and reduces monotonous instruction. However, implementation was not simultaneous; teachers sequenced the four skills within 80-minute lessons, prioritizing spoken skills before written skills and using one skill as the main target. Lesson-plan analysis confirmed that complex task-based integration was the dominant model. This study contributes empirical evidence on teacher-mediated ISA implementation in Indonesian elementary EFL contexts and highlights the need for clearer textbook support, richer listening resources, and explicit teacher training on integrated-skill lesson design.